Directory - American Psychological Association (Washington American Psychological Association, 1948)
Annual (Irregular)
Kept up-to-date between editions by: American Psychological Association. Membership register.
Supersedes its yearbook.
Keywords: American Psychological Association -- Directories; Psychologists -- United States -- Directories; Psychology -- Directories